Development of Pterygoquadrate Complex in the Embryogenesis of the Sand Lizard, Lacerta agilis (Reptilia, Squamata) - Yarygin, A.N. (Вестник зоологии, 2010)
Serial sections of 15 L. agilis embryos on the successive developmental stages, stained with hematoxylin-eosin or alcian blue and hematoxylin-eosin, were examined. It was found that cartilaginous pterygoquadrate complex of L. agilis consists of four parts: quadrate cartilage, pterygoquadrate cartilage, pterygoid process, and processus ascendens. Pterygoquadrate cartilage and pterygoid process are reduced in prenatal ontogenesis, but not earlier than underlying pterygoid bone is developed. The processus ascendens becomes the first cartilaginous parts of this complex, and then the other elements undergo chondrification. Basipterigoid process is formed by two independent parts: aboral part of cranial trabeculas and basipterigoid cartilage. Meniscus pterygoideus is an independent structure, but not a rudiment of the pterygoid process. A previously unrecorded cartilage was revealed and a name basipterigoid cartilage is proposed for it. Общепринятыми гистологическими методами исследовано 15 эмбрионов последовательных стадий развития прыткой ящерицы. Установлено, что хрящевой крыловидно-квадратный комплекс прыткой ящерицы состоит из четырех частей: квадратного хряща, крыловидно-квадратного хряща и двух его отростков крыловидного и восходящего. В процессе развития крыловидно-квадратный хрящ и крыловидный отросток редуцируются, но не ранее чем разовьется подлежащая под ними крыловидная кость. Первым хрящевым элементом данного комплекса является восходящий отросток, после чего охрящевевают остальные элементы. Базиптеригоидный отросток формируется из двух независимых компонентов: аборальной части черепных трабекул и базиптеригоидного хряща. Meniscus pterygoideus — самостоятельная структура, которая не является рудиментом крыловидного отростка. Выявлена неописанная ранее структура, которую мы предлагаем назвать базиптеригоидным хрящом.